PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERIS 50 BENGKALIS - Musyafak, Ibnu; Noviana, Eddy; Syahrilfudin, Syahrilfudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Snowball throwing learning is one of cooperative learning models, with emphasis on group learning system. Snowball throwing learning training students to be more responsive to receive a messages from others and convey a message to a friend of the group. The purpose of this study was to determine the effectiveness of the application of learning models snowball throwing to improve social subject outcomes in fourth grade students of SDN 50 Bengkalis. Design of this research is the Classroom Action Research which consists of four stages in each cycle, including planning, implementation, observation, and reflection. This study was conducted by two cycles. The reflection results in the first cycle showed that the teacher activity has been good and the student activity could be categorized well but there are still some things that need to be improved, likes the involvement of students in the classroom, students activity in the discussion. For the second cycle of teacher activity and students has been increased and has started better than ever. The results of data analysis and discussion of students learning outcomes in the first cycle showed that an increase in individuals where the number of students who completed the basic score as many as seven students with a percentage (35%) and the average value of 68.5 increased in the first cycle to 15 students the percentage (75%) and the average value of 77. in the second cycle increased to 18 students with a percentage (90%) and the average value of 85 so that it can be concluded that the implementation of Snowball Throwing learning models can improve the social subject grade IV SDN 50 Bengkalis.Keywords : Model , Snowball Throwing Learning , Learning Outcomes